2011
DOI: 10.1128/aem.00426-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orally Administered Bdellovibrio bacteriovorus on the Well-Being and Salmonella Colonization of Young Chicks

Abstract: Bdellovibrio bacteriovorus is a bacterium which preys upon and kills Gram-negative bacteria, including the zoonotic pathogens Escherichia coli and Salmonella. Bdellovibrio has potential as a biocontrol agent, but no reports of it being tested in living animals have been published, and no data on whether Bdellovibrio might spread between animals are available. In this study, we tried to fill this knowledge gap, using B. bacteriovorus HD100 doses in poultry with a normal gut microbiota or predosed with a coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 56 publications
8
134
0
1
Order By: Relevance
“…In the study mentioned earlier done by Atterbury et al (21), oral administration of BALOs to young http://bmbreports.org BMB reports chicks pre-dosed with a gut colonizing S. enterica found that these predatory strains could effectively attack Salmonella, thereby reducing its number in the cecum and significantly mitigating cecal inflammation caused by the infection. B. bacteriovorus was also found to decrease the severity of keratoconjuctivitis caused by Shigella flexneri in rabbit eyes provided that they were administrated in the first 48 hr of infection (19).…”
Section: Use Of Balos With Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study mentioned earlier done by Atterbury et al (21), oral administration of BALOs to young http://bmbreports.org BMB reports chicks pre-dosed with a gut colonizing S. enterica found that these predatory strains could effectively attack Salmonella, thereby reducing its number in the cecum and significantly mitigating cecal inflammation caused by the infection. B. bacteriovorus was also found to decrease the severity of keratoconjuctivitis caused by Shigella flexneri in rabbit eyes provided that they were administrated in the first 48 hr of infection (19).…”
Section: Use Of Balos With Animalsmentioning
confidence: 99%
“…A search of the literature shows that different research groups around the world are concentrating more on this area nowadays (20)(21)(22)(23)(24)(25), with all of these studies being published within the last two years. They include research characterizing B. bacteriovorus in different animal hosts, including chicks (21) and cows, particularly their tears (22), and evaluated its effects on various pathogens, such as Helicobacter pylori (20) bacterial agent to address real environmental, industrial and medical issues and to define both the advantages and challenges that face B. bacteriovorus as both a promising probiotic and an alternative for antibiotics in the future.…”
Section: Ushering In the Therapeutic Balo Period (2011-)mentioning
confidence: 99%
“…They hunt other pathogenic and/or potentially pathogenic bacteria in water and biofilms (10), and the spectrum of bacteria on which they prey is very nonspecific (9,11). BALOs have also been shown to be unable to prey on eukaryotic cells and as such pose no direct risk to human or animal health (12)(13)(14)(15). These features make BALOs possible candidates as biocontrol agents (10,11,16,17).…”
mentioning
confidence: 99%
“…Other uses involve the treatment of various infections in animals, including bovine keratoconjunctivitis caused by Moraxella bovis (5), Aeromonas hydrophila in fish (6,7), Vibrio cholerae and Proteus penneri in shrimp (8,9), and Salmonella enterica serovar Enteritidis in the chicken gut (10). They have also been applied in the treatment of human disease pathogens, including Pseudomonas aeruginosa from the lungs of cystic fibrosis patients (11), Pseudomonas aeruginosa and Serratia marcescens associated with eye infections (12), and oral pathogens that cause periodontal diseases (13,14).…”
mentioning
confidence: 99%